Lichen Family Lobariaceae Diversity as Air Pollution Bioindicator on Conservation National Park Gunung-Gede Pangrango (TNGGP) - Lilis Supratman (Journal of Tropical Ethnobiology, 2023)
Lichen is a symbiosis between fungi and algae. Lichen family Lobariaceae is a group of foliose that is very sensitive to air pollution. This study used lichen explorations in Gunung-Gede Pangrango National Park (TNGGP) area which is good for biodiversity reservoir as a method. During exploration, on ascending tracks of Curug Cibeureum, Lobaria pulmonaria was found. The main characteristic of L. pulmonaria is they have isidia, lobulus, tomentum, cephalodium, and rhizine squares types, are reactive to the K + reaction test, have wavy lobus, and look like resemble lungs and photobiont as green algae. It also can be found in tree trunk substrate at an elevation above 1 to 2 Meters. The tree barks' characteristic which is being overgrown by L. pulmonaria woody, rough surface, moist, wet, and has gemma (bud). According to the lobus abundance indicator and wide lobus, it can be concluded that air quality in TNGGP ascending tracks of Curug Cibeureum has an excellent category.